(3GdEeJfGY h GdeDGfSI (B2 :s (3GdLRA GdJGfj (B/s - (3GdJhMjOj, CHhMjGfs; (3eNJGQ(B;(3HdbGjOs ((3GdLhGFQ (B:s (3ehae ddfTQh GdJhRjY ,s, 1989)
(3cJGH YXje GdaGFOI ZRjQ GdeGOI eeJY eDfS ceG jhMj HPdc YfhGfg Gdag GHh MjGf dUOjbg hhdj fYeJg GHj GdhaGA eMeO Hf eMeO Hf jMj GdHhRLGfj GdQjGVj GdTgjQ jUa dg ajg eLGdS GdhRjQ GHf SYOGf h jQhj dg eGOGQ ajgG ef GMGOjK JJfGhd HGdHMK eNJda GdbVGjG GdYdejI h GdafjI ef GOH h dZI h abg h adSaI h Yde GLJeGY h SjGSI h Ydhe ObjbI h GdEeJfGY h GdeDGfSI PNjQI dGJfaO h cfR ef cfhR GdGOH GdYQHj HeGOJg GdKQjI h GSdhHg GdfGUY h efWbg Gdbhjs
Keywords: (3adSaIs; (3Yde GdELJeGYs; (3GdCOH GdYQHjs